Kerala and Carnatic Music - Sruthy Chandrasekhar (Integrated Journal for Research in Arts and Humanities, 2022)
In this chapter, keeping in mind the historical perspective of music in Kerala from pre-historic times, the evolution of Carnatic music from secular music in Kerala over a period of time has been enumerated and studied in detail.